2003
DOI: 10.1073/pnas.1531970100
|View full text |Cite
|
Sign up to set email alerts
|

Retinal counterion switch in the photoactivation of the G protein-coupled receptor rhodopsin

Abstract: The biological function of Glu-181 in the photoactivation process of rhodopsin is explored through spectroscopic studies of site-specific mutants. Preresonance Raman vibrational spectra of the unphotolyzed E181Q mutant are nearly identical to spectra of the native pigment, supporting the view that Glu-181 is uncharged (protonated) in the dark state. The pH dependence of the absorption of the metarhodopsin I (Meta I)-like photoproduct of E181Q is investigated, revealing a dramatic shift of its Schiff base pKa c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
280
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(307 citation statements)
references
References 38 publications
25
280
1
1
Order By: Relevance
“…Such dimers do not exist in the single photon working range (36) of the rod photoreceptor cell. Furthermore, it remains to be studied how the sequence of catalytic steps in R*-G protein coupling identified here relate to different conformations of the activated receptor, which are separated by protonation changes in rhodopsin (2,(37)(38)(39)(40)(41). The G protein may use different receptor conformations, which can bind either CT␣ or CT␥-far, to allosterically control the affinity of the two binding sites on the receptor for efficient nucleotide exchange catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Such dimers do not exist in the single photon working range (36) of the rod photoreceptor cell. Furthermore, it remains to be studied how the sequence of catalytic steps in R*-G protein coupling identified here relate to different conformations of the activated receptor, which are separated by protonation changes in rhodopsin (2,(37)(38)(39)(40)(41). The G protein may use different receptor conformations, which can bind either CT␣ or CT␥-far, to allosterically control the affinity of the two binding sites on the receptor for efficient nucleotide exchange catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…The only GPCR transmembrane structure available is that of rhodopsin in the inactive form (Palczewski et al, 2000), and, despite a plethora of informative biophysical studies on rhodopsin (Farrens, 1996;Dunham and Farrens, 1999;Meng and Bourne, 2001;Choi et al, 2002;Yan et al, 2003), there remains a paucity of information of the exact nature of the intramolecular changes accompanying receptor activation. In the past several years, a great deal has been learned from modeling the endodomain of LHR using ab initio and, more recently, comparative modeling approaches (Fanelli, 2000;Fanelli et al, 2001Fanelli et al, , 2004Fanelli and Puett, 2002;Fanelli and De Benedetti, 2005;Angelova et al, 2002;Ascoli et al, 2002;Zhang et al, 2005).…”
Section: Activation Of the Transmembrane Region Of Lhrmentioning
confidence: 99%
“…Some experimental evidence has suggested that Glu 181 is protonated in the dark-adapted state, but transfers its proton to Glu 113 via Ser 186 and then replaces Glu 113 as the PSB counterion. 32 Other work suggests that both Glu 113 and Glu 181 are unprotonated and that both act as the PSB counterion, with Glu 181 dominating in the Meta I state. 33 We have simulated both Glu 113 and Glu 181 in their unprotonated states, and we find that structural changes occur that could lead to the PSB counterion switching from Glu 113 to Glu 181.…”
Section: Psb Counterion Switchmentioning
confidence: 99%
“…11,32,[54][55][56][57][58][59][60][61][62][63][64][65] This would involve a change in protonation states during the photocycle 33 and experimental work has confirmed that Glu 113 is the dark-state counterion and been suggestive, but not conclusive, that Glu 181 is active during the light-activated stages. 66,67 The simulation results are intriguing in suggesting that this counterion switch mechanism could be present as part of the relaxation mechanism of the protein to the retinal conformational change.…”
Section: Counterion Switchmentioning
confidence: 99%